Education Alignment and Accountability in an Era of Convergence: Policy Insights from States with Individual Learning Plans and Policies - Phelps, L. Allen; Durham, Julie; Wills, Joan (Education Policy Analysis Archives, 2011)
In response to the rising demand for market-responsive education reform across the U.S., since 1998 more than twenty states have created individual learning or graduation plan (ILP/IGP) state policies. Using extensive policy document analyses and stakeholder interview data from four early-adopting ILP/IGP states, the goal of this four-state case study was twofold. First, to determine the extent to which states are leveraging federal and state resources to align their ILP initiatives with other policies aimed at fostering education innovation and assisting economic recovery. The second goal was to develop policy recommendations for making intergovernmental investments to strengthen performance outcomes in education and workforce development in ILP/IGP states. The federal interest in equal protection and improving equity for special populations including youth with disabilities stimulated and animated the investigation. Several key findings emerged across the four states. First, to date limited fiscal investments in professional development and systematic data collection have constrained ILP-IGP implementation and evaluation efforts. Second, the opportunity to align and leverage the state investment with federal programs and other state employment and education initiatives was largely unexplored in these states. Recommendations for state policy improvements include aligning ILP policies with state plans for improving outcomes in federal programs for students confronting economic, language and disability challenges.